3D photogrammetric analysis in hump nose correction based on nasal tip projection without dorsal augmentation in Asian rhinoplasty. Issue 8 (August 2020) - Kim, Min Ji; Jeon, Dong Nyeok; Choi, Jong Woo; Chan Kim, Sung
Abstract: Introduction: Hump nose in Asians should be managed differently in consideration of the lateral profile and the balance between the dorsal height and nasal tip projection. We suggest an alternative approach comprising mild rasping and nasal tip projection using a septal extension graft. Material and methods: In this retrospective study, patients who underwent hump nose correction with rhinoplasty between March 2012 and July 2015 were recruited. Instead of applying conventional dorsal augmentation after humpectomy, our approach involved only smooth dorsal contouring in limited cases. 15 patients were evaluated, with surgical outcomes demonstrated using three-dimensional photogrammetry. Results: Over the postoperative period, hump height decreased (pre 2.77 ± 2.07, post 0.31 ± 0.55, p = 0.001). Regarding the efficacy of tip projection, both nasal tip protrusion (pre 17.64 ± 4.82, post 20.46 ± 4.05, p = 0.001) and tip projection (pre 19.75 ± 4.26, post 21.83 ± 4.17, p = 0.023) were increased. The hump nose reduction ratio was 84.94% after 6 months and 76.47% after 1 year, whereas increases in nasal tip projection and dorsal augmentation were minimal, with ratios of 14.75% and 12.76%, respectively, after 6 months). Conclusion: Therefore, creating a balance between the nasal tip and nasal dorsum in hump nose correction is more important than dorsal augmentation after hump resection in Asians.